2018
DOI: 10.3920/wmj2017.2282
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence ofAlternaria mycotoxins and quantification of viableAlternaria spp. during the food processing of tomato products in Spain

Abstract: The occurrence of two Alternaria mycotoxins, alternariol (AOH) and alternariol monomethyl ether (AME) and the presence of conidia from Alternaria spp., were investigated throughout the food production chain of two businesses, one which uses organic fruit and the other non-organic. For this purpose, a propidium monoazide (PMA) treatment followed by a quantitative Real Time PCR (qPCR) was used to detect and quantify viable conidia exclusively. Results demonstrated that 68.4% of the total raw fruit analysed was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Tomato and its products are one of the critical targets for contamination by Alternaria toxins. For example, Alternaria toxins were detected in Brazilian tomatoes and their derivatives, where 68.4% of the original samples were contaminated with A. alternata [ 22 ]. Sanzani et al analyzed dried and fresh tomato samples from Southern Italian markets and processing factories for toxins, and they found that all of the samples were contaminated with TeA, with AME coming up second, then TEN, and AOH [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tomato and its products are one of the critical targets for contamination by Alternaria toxins. For example, Alternaria toxins were detected in Brazilian tomatoes and their derivatives, where 68.4% of the original samples were contaminated with A. alternata [ 22 ]. Sanzani et al analyzed dried and fresh tomato samples from Southern Italian markets and processing factories for toxins, and they found that all of the samples were contaminated with TeA, with AME coming up second, then TEN, and AOH [ 23 ].…”
Section: Introductionmentioning
confidence: 99%